Pengaruh Penyaluran ZIS, Pertumbuhan Ekonomi, Pengangguran, dan Pendapatan Asli Daerah terhadap Tingkat Kemiskinan di Provinsi Sumatera Barat Periode 2020-2024 - Aufa Aufiya; Eva Ervani (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to analyze the effect of the distribution of Zakat, Infak, and Sadaqah (ZIS) funds, economic growth, unemployment rate, and Regional Original Revenue (PAD) on the poverty rate in West Sumatra Province during the period 2020–2024. The data used are secondary data obtained from BAZNAS, BPS, and the Directorate General of Fiscal Balance (DJPK), covering 12 regencies/cities in West Sumatra Province. This study employs panel data regression analysis using EViews 12 software to examine the relationships among the variables. The results indicate that, partially, the distribution of ZIS funds and PAD have no significant effect on the poverty rate. In contrast, economic growth and unemployment rate have a negative and significant effect on the poverty rate. Simultaneously, all four independent variables are found to have a significant influence on the poverty rate. The coefficient of determination (Adjusted R²) is 0.123, indicating that 12.30% of the variation in the poverty rate can be explained by the variables in the study, while the remaining 87.7% is influenced by factors outside the model. The study provides policy implications suggesting that optimizing ZIS management, promoting inclusive economic growth, expanding employment opportunities to reduce unemployment, and utilizing PAD more effectively are crucial strategies for local governments and relevant institutions to effectively reduce the poverty rate in West Sumatra.